2018
DOI: 10.3390/ijerph15050960
|View full text |Cite
|
Sign up to set email alerts
|

Advice and Frequently Asked Questions (FAQs) for Citizen-Science Environmental Health Assessments

Abstract: Citizen science provides quantitative results to support environmental health assessments (EHAs), but standardized approaches do not currently exist to translate findings into actionable solutions. The emergence of low-cost portable sensor technologies and proliferation of publicly available datasets provides unparalleled access to supporting evidence; yet data collection, analysis, interpretation, visualization, and communication are subjective approaches that must be tailored to a decision-making audience ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…The volunteers brought up various options and suggestions regarding what could be done in the future with low-cost portable air quality sensor systems. Similarly, Barzyk et al [ 65 ] collected Newark’s Ironbound community’s suggestions on what would be the next steps with regards to sensor technologies. The volunteers in our study suggested that such devices have the potential for raising awareness about the spatial distribution of air pollution, which could affect preferred routes and places to spend time and live in, and hence, improve one’s quality of life.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The volunteers brought up various options and suggestions regarding what could be done in the future with low-cost portable air quality sensor systems. Similarly, Barzyk et al [ 65 ] collected Newark’s Ironbound community’s suggestions on what would be the next steps with regards to sensor technologies. The volunteers in our study suggested that such devices have the potential for raising awareness about the spatial distribution of air pollution, which could affect preferred routes and places to spend time and live in, and hence, improve one’s quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…In order to reduce costs for the end users of low-cost portable air quality sensing systems, a rental service operating through either a company or a research institute for individuals and schools was suggested. A sensor loan program for public use has already been suggested by Barzyk et al [ 65 ]. Moreover, volunteers expressed their interest in wanting to know about the air quality in their own neighborhood, and wished for such devices to be used to determine where the air quality is poor and how to improve it.…”
Section: Resultsmentioning
confidence: 99%
“…These sensors have light weights (230, 55, and 18 g, respectively) and compact sizes to be used as low-burden personal monitors for pregnant women. MicroPEM, CairClip and Ogawa badges were the best available technologies for wearable sensors when those real-time sensors were chosen in 2015 [ 20 , 21 , 22 ]. Prior to each MicroPEM deployment, each individual MicroPEM’s flow rate and baseline response were calibrated [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…If response plans lack transparency, a CBM partner who encounters a sample that contains a high level of an indicator organism, but upon subsequent tests shows low or no risk, might be dismayed by a lack of response by government. A CBM qPCR monitoring system in recreational water would need to prioritize communication and understanding between regulators and CBM partners, and would likely function best when addressing specific objectives [36].…”
Section: Future Directions For the Cbm Qpcr Programmentioning
confidence: 99%